Display and adhesive sheet
By using a white colorant with a color difference of less than 95 and a high total light transmittance in the display body, the visibility problem caused by the light-shielding and light-hidden design of the display body adhesive sheet in the prior art is solved. , improves designability and visibility, and maintains excellent segment difference following under high temperature and high humidity conditions.
Patent Information
- Application Number
- CN202011079907.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-10-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-10-10
AI Technical Summary
The design of the adhesive sheet used for display bodies in the prior art in terms of light shielding and light concealment results in the fact that when the liquid crystal module or organic EL module is approaching the viewer side, the visibility of the display image cannot be ensured, which affects the designability and ability. Vision.
It provides an adhesive sheet, wherein the color difference ΔE* of the adhesive layer is less than 95, the total light transmittance is more than 10%, and contains a white colorant, preferably an acrylic adhesive, which is cross-linked from (meth)acrylate polymer. The agent and a white colorant are composed of an adhesive layer between the display body constituent members, ensuring coordination with the surrounding members when the lamp is turned off, and image visibility is ensured when the lamp is turned on.
The design and visibility of the display body are improved, ensuring the appearance coordination and image visibility of the display body under different lighting conditions, while providing excellent segment difference following and adhesion.
Smart Images

Figure CN112646507B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a display body and an adhesive sheet used for the display body. Background Art
[0002] In recent years, image display devices such as liquid crystal display devices and organic electroluminescent (organic EL) devices are increasingly used in display bodies (displays), such as televisions, computer monitors (monitors), digital signage, smartphones, tablet terminals, etc.
[0003] For the display body as described above, it is sometimes required that the display body, when the light is off, reflects a sense of integration with the surrounding components of the display body, such as the frame material, to improve the design. For this reason, it is possible to consider coloring the display body. For example, Patent Document 1 discloses a technology related to coloring of the display body.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-82634 Summary of the invention
[0007] Technical Problems to be Solved by the Invention
[0008] However, since the adhesive sheet disclosed in Patent Document 1 is colored for light shielding and light concealing properties, visibility of displayed images cannot be ensured when the adhesive sheet is used on the side closer to the viewer than a liquid crystal module or an organic EL module.
[0009] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide an adhesive sheet capable of improving the design of a display, and a display with improved design.
[0010] Technical means to solve technical problems
[0011] In order to achieve the above-mentioned purpose, first, the present invention provides an adhesive sheet, which has an adhesive layer for bonding a display body component to another display body component, and the adhesive sheet is characterized in that the color difference ΔE* between the adhesive layer and pure white specified by the CIE1976L*a*b* color system is less than 95, and the total light transmittance of the adhesive layer is greater than 10% (Invention 1).
[0012] In the above invention (Invention 1), by making the color difference ΔE* of the adhesive layer as described above, when the display body is turned off, the appearance coordination with the white surrounding components can be sought, and the design is improved. In addition, in the above invention (Invention 1), by making the total light transmittance of the adhesive layer as described above, the visibility of the image and video can be ensured when the display body is turned on.
[0013] In the above invention (Invention 1), it is preferred that the haze value of the pressure-sensitive adhesive layer is 0.5% or more and 100% or less (Invention 2).
[0014] In the above inventions (Inventions 1 and 2), it is preferred that the adhesive layer is composed of an adhesive containing a white coloring agent (Invention 3).
[0015] In the above inventions (Inventions 1 to 3), it is preferred that the content of the white colorant in the adhesive is 0.01% by mass or more and 50% by mass or less (Invention 4).
[0016] In the above inventions (Inventions 1 to 4), it is preferred that the adhesive is an acrylic adhesive (Invention 5).
[0017] In the above inventions (Inventions 1 to 5), the adhesive is preferably formed by crosslinking an adhesive composition containing at least a (meth)acrylate polymer (A), a crosslinking agent (B) and a white colorant (C) (Invention 6).
[0018] In the above inventions (Inventions 1 to 6), it is preferred that two release sheets and the adhesive layer are provided, and the adhesive layer is sandwiched by the release sheets so as to be in contact with release surfaces of the two release sheets (Invention 7).
[0019] Second, the present invention provides a display body comprising: a display body constituent member, another display body constituent member, and an adhesive layer for bonding the one display body constituent member and the other display body constituent member to each other, wherein the display body is characterized in that the adhesive layer is formed by the adhesive layer of the adhesive sheet (Inventions 1 to 7) (Invention 8).
[0020] In the above invention (Invention 8), preferably, at least one of the one display constituting member and the other display constituting member has a step on a surface on a side to be bonded by the adhesive layer (Invention 9).
[0021] In the above inventions (Inventions 8 and 9), it is preferable to have a white surrounding member (Invention 10).
[0022] Effects of the Invention
[0023] According to the adhesive sheet of the present invention, the design of the display can be improved. In addition, the design of the display of the present invention is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a cross-sectional view of an adhesive sheet according to one embodiment of the present invention.
[0025] Figure 2This is a cross-sectional view of a display according to one embodiment of the present invention.
[0026] Figure 3 This is a plan view of a display body having a frame material according to one embodiment of the present invention.
[0027] Description of Reference Numerals
[0028] 1: adhesive sheet; 11: adhesive layer; 12a, 12b: release sheets; 2: display body; 21: first display body component; 22: second display body component; 3: printed layer; 4: frame material. DETAILED DESCRIPTION
[0029] Hereinafter, embodiments of the present invention will be described.
[0030] [Adhesive sheet]
[0031] The adhesive sheet of one embodiment of the present invention comprises an adhesive layer for bonding one display component to another display component, and is preferably formed by laminating a release sheet on one or both sides of the adhesive layer. The display and the display component will be described later.
[0032] Figure 1 Detailed structure of an example of the adhesive sheet according to the present embodiment is shown in FIG.
[0033] like Figure 1 As shown, the adhesive sheet 1 is composed of two release sheets 12a, 12b and an adhesive layer 11, and the adhesive layer 11 is sandwiched by the two release sheets 12a, 12b in a manner of contacting the release surfaces of the two release sheets 12a, 12b. In addition, the release surface of the release sheet in this specification refers to a surface of the release sheet that has a release property, including any one of a surface that has been subjected to a release treatment and a surface that exhibits a release property even if a release treatment is not applied.
[0034] 1. Each component
[0035] 1-1. Adhesive layer
[0036] The adhesive layer 11 of the adhesive sheet 1 of the present embodiment has a color difference ΔE* from pure white as defined by the CIE 1976 L*a*b* colorimetric system of less than 95, and a total light transmittance of 10% or more.
[0037] The pure white color specified by the CIE1976 L*a*b* color system has a lightness L* of 100, a chromaticity a* of 0, and a chromaticity b* of 0. Therefore, for the adhesive layer 11, when the measured value of the lightness L* is set to L*M, the measured value of the chromaticity a* is set to a*M, and the measured value of b* is set to b*M, the color difference ΔE* between the pure white color and the pure white color can be calculated by the following formula (I).
[0038] [Mathematical formula 1]
[0039]
[0040] In addition, the measurement method (reflected light measurement) of the lightness L*, chromaticity a* and b* in this specification is as shown in the test examples described later.
[0041] In the adhesive sheet 1 of this embodiment, by making the color difference ΔE* of the adhesive layer 11 as described above, when the display body is turned off, the appearance coordination with the white surrounding components, such as the appearance coordination with the white frame material, the white wall, the white printed part, etc., can be sought, and the design is improved. In addition, the white color of the surrounding components does not necessarily have to be the above-mentioned "pure white".
[0042] In the adhesive sheet 1 of the present embodiment, the total light transmittance of the adhesive layer 11 is 10% or more, so that the visibility of images and videos can be ensured when the display is lit. The total light transmittance in this specification is a value measured in accordance with JIS K7361-1:1997.
[0043] From the perspective of appearance coordination with white surrounding components, the color difference ΔE* must be less than 95, preferably 80 or less, more preferably 60 or less, particularly preferably 40 or less, and further preferably 35 or less. The lower limit of the color difference ΔE* is not particularly limited, and the minimum value is 0, but considering the relationship with the total light transmittance, it is preferably 1 or more, more preferably 5 or more, particularly preferably 10 or more, and further preferably 20 or more.
[0044] The lightness L*M of the adhesive layer 11 is preferably 3 or more, more preferably 9 or more, particularly preferably 50 or more, and further preferably 65 or more. In addition, the lightness L*M is preferably 100 or less, more preferably 90 or less, particularly preferably 83 or less, and further preferably 80 or less. The absolute value of the chromaticity a*M of the adhesive layer 11 is preferably 0 or more, particularly preferably 0.1 or more, and further preferably 0.5 or more. In addition, the absolute value of the chromaticity a*M is preferably 10 or less, more preferably 5 or less, particularly preferably 2 or less, and further preferably 1.5 or less. The absolute value of the chromaticity b*M of the adhesive layer 11 is preferably 0 or more, and particularly preferably 0.1 or more. In addition, the absolute value of the chromaticity b*M is preferably 10 or less, more preferably 5 or less, particularly preferably 2 or less, and further preferably 1.5 or less. By setting it as above, it is easy to satisfy the above-mentioned color difference ΔE* and total light transmittance, and at the same time have a preferred color tone when the display body is turned off.
[0045] From the perspective of image and video visibility, the total light transmittance of the adhesive layer 11 must be 10% or more, preferably 20% or more, more preferably 30% or more, particularly preferably 40% or more, and further preferably 45% or more. The upper limit of the total light transmittance is usually 100% or less, and considering the relationship with the above-mentioned color difference ΔE*, it is preferably 95% or less, more preferably 90% or less, particularly preferably 80% or less, further preferably 70% or less, and most preferably 65% or less.
[0046] The haze value of the adhesive layer 11 is preferably 0.5% or more, more preferably 5% or more, particularly preferably 15% or more, further preferably 60% or more, and most preferably 90% or more. Thus, it is easy to satisfy the above-mentioned color difference ΔE*, and it is easier to give the resulting display a sense of integrity with the surrounding white components. In addition, the upper limit of the haze value of the adhesive layer 11 is not particularly restricted, but is preferably 100% or less, more preferably 99.9% or less, particularly preferably 99.8% or less, and further preferably 99.4% or less. In addition, the haze value in this specification is set to a value measured in accordance with JIS K7136:2000.
[0047] The adhesive constituting the adhesive layer 11 preferably contains a white colorant. By appropriately selecting the type and content of the white colorant, the above-mentioned color difference ΔE* and total light transmittance (and haze value) can be achieved.
[0048] The above-mentioned white coloring agent may be mainly composed of a pigment or a dye. The pigment may be an inorganic pigment or an organic pigment. From the perspective of the durability of the obtained adhesive, an inorganic pigment is preferred.
[0049] White colorants preferably contain inorganic pigments such as titanium oxide, zinc oxide, calcium carbonate, and aluminum oxide. From the perspective of being able to maintain a high total light transmittance even when ΔE* is low, titanium oxide and zinc oxide are more preferred, and titanium oxide is particularly preferred. These inorganic pigments may also be subjected to surface treatments such as organic treatment, silicone treatment, and aluminum oxide treatment. The above-mentioned inorganic pigments may be used alone or in combination of two or more.
[0050] In addition, the above-mentioned white coloring agent may also contain inorganic pigments and colorless transparent particles such as silicon dioxide. Thus, it is easy to obtain a suitable white color. At this time, the content of the colorless transparent particles in the white coloring agent is preferably 0.01 to 50% by mass, more preferably 0.1 to 30% by mass, particularly preferably 1 to 20% by mass, and further preferably 5 to 10% by mass.
[0051] The mode diameter (mode diameter) of the white colorant is preferably 2 nm or more, more preferably 10 nm or more, particularly preferably 100 nm or more, and further preferably 200 nm or more. Thus, it is easy to satisfy the above-mentioned color difference ΔE*. In addition, the above-mentioned mode diameter is preferably 3000 nm or less, more preferably 1000 nm or less, particularly preferably 800 nm or less, and further preferably 600 nm or less. Thus, it is easy to satisfy the above-mentioned total light transmittance.
[0052] The median particle size (D50) of the white colorant is preferably 2 nm or more, more preferably 10 nm or more, particularly preferably 100 nm or more, and further preferably 200 nm or more. Thus, it is easy to satisfy the above-mentioned color difference ΔE*. In addition, the above-mentioned median particle size is preferably 3000 nm or less, more preferably 1000 nm or less, particularly preferably 800 nm or less, and further preferably 600 nm or less. Thus, it is easy to satisfy the above-mentioned total light transmittance.
[0053] In addition, the mode diameter and median diameter of the white colorant in this specification are values measured by a dynamic light scattering method.
[0054] The content of the white coloring agent in the adhesive constituting the adhesive layer 11 is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 1% by mass or more, and further more preferably 3% by mass or more. Thus, even if the adhesive layer is not too thick, it is easy to satisfy the above-mentioned color difference ΔE*. In addition, the above-mentioned content is preferably 50% by mass or less, more preferably 30% by mass or less, particularly more preferably 20% by mass or less, and further more preferably 15% by mass or less. If the angle of thinning the adhesive layer and making the step tracking excellent is taken into account, it is preferably 8% by mass or less. Thus, it is easy to satisfy the above-mentioned total light transmittance.
[0055] From the perspective of the relationship with the content of the white colorant and the ease of satisfying the above-mentioned optical properties, the thickness of the adhesive layer 11 is preferably 3 μm or more, more preferably 10 μm or more, and particularly preferably 20 μm or more, based on the following limit values. If the perspective of further improving the step tracking property is taken into account, it is preferably 40 μm or more.
[0056] In addition, the thickness of the adhesive layer 11 is preferably 3000 μm or less, more preferably 1000 μm or less, particularly preferably 500 μm or less, and further preferably 300 μm or less, based on the upper limit. If the upper limit of the thickness of the adhesive layer 11 is as above, it is easy to satisfy the above optical properties due to the relationship with the content of the white coloring agent. In addition, it is not easy to produce poor appearance caused by extrusion marks, etc.
[0057] The adhesive layer 11 may be formed of a single layer or may be formed by laminating a plurality of layers. In addition, the thickness of the adhesive layer 11 in this specification is a value measured in accordance with JIS K7130.
[0058] The type of adhesive constituting the adhesive layer 11 of the adhesive sheet 1 of the present embodiment is not particularly limited, and may be, for example, any one of acrylic adhesives, polyester adhesives, polyurethane adhesives, rubber adhesives, silicone adhesives, etc. In addition, the adhesive may be any one of an emulsion type, a solvent type, or a solvent-free type, and may be any one of a cross-linked type or a non-cross-linked type. Among them, acrylic adhesives having excellent adhesive properties, optical properties, etc. are preferred.
[0059] In addition, the acrylic adhesive may be an active energy ray-curable acrylic adhesive or an inactive energy ray-curable acrylic adhesive. In addition, the acrylic adhesive is preferably a cross-linked acrylic adhesive, and more preferably a thermally cross-linked acrylic adhesive.
[0060] Specifically, the adhesive is preferably formed by cross-linking an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing at least a (meth)acrylate polymer (A), a crosslinking agent (B) and a white colorant (C). In addition, when the adhesive is an active energy ray-curable adhesive, the adhesive composition P preferably further contains an active energy ray-curable component (D).
[0061] The adhesive obtained by the adhesive composition P can exert excellent optical properties, adhesion, durability (step difference tracking under high temperature and high humidity conditions), etc. In addition, in this specification, (meth) acrylic acid refers to acrylic acid and methacrylic acid. Other similar terms are also the same. In addition, "polymer" also includes the concept of "copolymer".
[0062] (1) Components of the adhesive composition
[0063] (1-1) (Meth)acrylate polymer (A)
[0064] The (meth)acrylate polymer (A) of the present embodiment preferably contains a reactive group-containing monomer as a monomer unit constituting the polymer, and the reactive group-containing monomer has a reactive group in the molecule that reacts with the crosslinking agent (B). By reacting the reactive group from the reactive group-containing monomer with the crosslinking agent (B), a crosslinked structure (three-dimensional network structure) can be formed, and an adhesive having a desired cohesive force can be obtained.
[0065] As the above-mentioned reactive group-containing monomer, preferably there can be mentioned a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. Among them, a hydroxyl group-containing monomer or a carboxyl group-containing monomer having excellent reactivity with the crosslinking agent (B) is preferred, and a hydroxyl group-containing monomer and a carboxyl group-containing monomer may be used simultaneously.
[0066] As the hydroxyl-containing monomer, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and other hydroxyalkyl (meth)acrylates, etc. can be cited. Among them, from the point of view of the reactivity of the hydroxyl group in the obtained (meth)acrylate polymer (A) with the crosslinking agent (B) and the copolymerizability of the hydroxyl group with other monomers, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 1 to 4 carbon atoms are preferred. Specifically, for example, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and the like can be preferably cited, and 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate can be particularly preferably cited. These hydroxyl-containing monomers can be used alone or in combination of two or more.
[0067] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Of these, acrylic acid is preferred from the perspective of the reactivity of the carboxyl group in the obtained (meth)acrylate polymer (A) with the crosslinking agent (B) and the copolymerizability of the carboxyl group with other monomers. These carboxyl-containing monomers may be used alone or in combination of two or more.
[0068] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These amino group-containing monomers may be used alone or in combination of two or more.
[0069] According to the following limit, the (meth) acrylate polymer (A) preferably contains more than 1% by mass, particularly preferably contains more than 5% by mass, and further preferably contains more than 10% by mass of reactive group-containing monomers as monomer units constituting the polymer. When the reactive group-containing monomer is only a hydroxyl-containing monomer, it is preferably more than 15% by mass, particularly preferably contains more than 20% by mass of reactive group-containing monomers as monomer units constituting the polymer. In addition, according to the upper limit, the (meth) acrylate polymer (A) preferably contains less than 40% by mass, particularly preferably contains less than 30% by mass, and further preferably contains less than 25% by mass of reactive group-containing monomers as monomer units constituting the polymer. If the (meth) acrylate polymer (A) contains a reactive group-containing monomer as a monomer unit in the above amount, a good cross-linked structure can be formed in the obtained adhesive to obtain the desired cohesive force. In addition, the dispersibility of the white colorant (C) in the adhesive tends to become good, and the reproducibility and uniformity of the above-mentioned optical properties of the obtained adhesive become good, and it is easy to meet the above-mentioned color difference ΔE*.
[0070] In addition, the (meth)acrylate polymer (A) also preferably does not contain a carboxyl-containing monomer as a monomer unit constituting the polymer. Since the carboxyl group is an acid component, by not containing a carboxyl-containing monomer, even when there is a substance that produces adverse conditions due to acid in the adhesive's attachment object, such as a transparent conductive film or metal film such as tin-doped indium oxide (ITO), the above-mentioned adverse conditions (corrosion, resistance value change, etc.) caused by the acid can be suppressed. However, it is also allowed to contain a specified amount of carboxyl-containing monomer to the extent that the above-mentioned adverse conditions are not generated. Specifically, in the (meth)acrylate polymer (A), it is allowed to contain a carboxyl-containing monomer as a monomer unit in an amount of less than 0.1% by mass, preferably in an amount of less than 0.01% by mass, and more preferably in an amount of less than 0.001% by mass.
[0071] The (meth)acrylate polymer (A) preferably contains an alkyl (meth)acrylate as a monomer unit constituting the polymer. This can exhibit good adhesiveness. The alkyl group may be linear or branched.
[0072] From the viewpoint of adhesiveness, the alkyl (meth)acrylate is preferably an alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms. Examples of the alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, and octadecyl (meth)acrylate. Among them, from the viewpoint of further improving adhesiveness, the alkyl (meth)acrylate having an alkyl group with 1 to 8 carbon atoms is preferred, and methyl (meth)acrylate, n-butyl (meth)acrylate, or 2-ethylhexyl (meth)acrylate is particularly preferred, and methyl methacrylate, n-butyl acrylate, or 2-ethylhexyl acrylate is further preferred. In addition, these alkyl (meth)acrylates may be used alone or in combination of two or more.
[0073] The (meth) acrylate polymer (A) preferably contains 40% by mass or more, particularly preferably 50% by mass or more, and further preferably 60% by mass or more of (meth) alkyl acrylate as a monomer unit constituting the polymer. If the lower limit of the content of the (meth) alkyl acrylate is as above, the (meth) acrylate polymer (A) can exert suitable adhesion. In addition, the dispersibility of the white colorant (C) in the adhesive tends to become good, and the (meth) acrylate polymer (A) can be inhibited from damaging the required adhesion. Thus, the obtained adhesive can exert suitable adhesion, and the reproducibility and uniformity of the above-mentioned optical properties become good, and it is easy to meet the above-mentioned color difference ΔE*. In addition, the (meth) acrylate polymer (A) preferably contains 99% by mass or less, more preferably 95% by mass or less, particularly preferably 90% by mass or less, and further preferably 85% by mass or less of (meth) alkyl acrylate as a monomer unit constituting the polymer. When the upper limit of the content of the alkyl (meth)acrylate is as described above, an appropriate amount of other monomer components such as a reactive functional group-containing monomer can be introduced into the (meth)acrylate polymer (A).
[0074] The (meth)acrylate polymer (A) also preferably contains a monomer having an alicyclic structure in the molecule (alicyclic structure-containing monomer) as a monomer unit constituting the polymer. Since the alicyclic structure-containing monomer is large in volume, it is speculated that by making it present in the polymer, the interval between the polymers is expanded, and the resulting adhesive can have excellent flexibility. As a result, the step followability of the adhesive becomes excellent.
[0075] The carbon ring of the alicyclic structure in the alicyclic structure-containing monomer may be a carbon ring of a saturated structure or a carbon ring having an unsaturated bond in a part. In addition, the alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure such as a bicyclic or tricyclic structure. From the perspective of making the distance between the obtained (meth)acrylate polymers (A) appropriate and imparting a higher stress relaxation to the adhesive, the alicyclic structure is preferably a polycyclic alicyclic structure (polycyclic structure). Further, considering the compatibility of the (meth)acrylate polymer (A) with other components, the polycyclic structure is particularly preferably a bicyclic to tetracyclic structure. In addition, as described above, from the perspective of imparting stress relaxation, the number of carbon atoms in the alicyclic structure (referring to the total number of carbon atoms in the part forming the ring, and when multiple rings exist independently, it refers to the total number of carbon atoms) is generally preferably 5 or more, and particularly preferably 7 or more. On the other hand, although the upper limit of the number of carbon atoms in the alicyclic structure is not particularly limited, it is preferably 15 or less, and particularly preferably 10 or less, from the perspective of compatibility as described above.
[0076] As the above-mentioned alicyclic structure-containing monomer, specifically, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. can be listed, among which dicyclopentyl (meth)acrylate (carbon number of alicyclic structure: 10), adamantyl (meth)acrylate (carbon number of alicyclic structure: 10) or isobornyl (meth)acrylate (carbon number of alicyclic structure: 7) are preferred, isobornyl (meth)acrylate is particularly preferred, and isobornyl acrylate is further preferred. These alicyclic structure-containing monomers can be used alone or in combination of two or more.
[0077] When the (meth)acrylate polymer (A) contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer, it is preferably 1% by mass or more, particularly preferably 4% by mass or more, and further preferably 8% by mass or more of the alicyclic structure-containing monomer. In addition, the (meth)acrylate polymer (A) preferably contains 30% by mass or less, particularly preferably 22% by mass or less, and further preferably 14% by mass or less of the alicyclic structure-containing monomer as a monomer unit constituting the polymer. By making the content of the alicyclic structure-containing monomer within the above range, the step tracking property of the obtained adhesive is more excellent, and the adhesion to plastics is further excellent.
[0078] In addition, the above-mentioned (meth)acrylate polymer (A) also preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. By making the nitrogen atom-containing monomer present in the polymer as a structural unit, the adhesive can be given a predetermined polarity, so that the adhesive has excellent affinity even for adherends with a certain degree of polarity such as glass. From the perspective of giving the (meth)acrylate polymer (A) suitable rigidity, the above-mentioned nitrogen atom-containing monomer is preferably a monomer having a nitrogen-containing heterocycle. In addition, from the perspective of increasing the degree of freedom of the part from the above-mentioned nitrogen atom-containing monomer in the high-dimensional structure of the constituted adhesive, it is preferred that the nitrogen atom-containing monomer does not contain a reactive unsaturated double bond group except for a polymerizable group used in the polymerization for forming the (meth)acrylate polymer (A).
[0079] As monomers having nitrogen-containing heterocyclic rings, for example, N-(methyl)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(methyl)acryloylpyrrolidone, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-(methyl)acryloylaziridine, aziridinylethyl(methyl)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, N-vinylphthalimide, etc. can be listed, among which N-(methyl)acryloylmorpholine having better adhesion is preferred, and N-acryloylmorpholine is particularly preferred. These monomers having nitrogen-containing heterocyclic rings can be used alone or in combination of two or more.
[0080] When the (meth)acrylate polymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer, it is preferably 1% by mass or more, particularly preferably 4% by mass or more, and further preferably 8% by mass or more of the nitrogen atom-containing monomer. In addition, the (meth)acrylate polymer (A) preferably contains 20% by mass or less, particularly preferably 16% by mass or less, and further preferably 12% by mass or less of the nitrogen atom-containing monomer as a monomer unit constituting the polymer. If the content of the nitrogen atom-containing monomer is within the above range, the resulting adhesive can fully exert excellent adhesion to glass.
[0081] The (meth)acrylate polymer (A) may contain other monomers as monomer units constituting the polymer as required. In order not to hinder the above-mentioned effects of the monomer containing reactive functional groups, as other monomers, monomers that do not contain reactive functional groups are preferably used. As such monomers, for example, (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, styrene, etc. can be listed. These other monomers can be used alone or in combination of two or more.
[0082] The (meth)acrylate polymer (A) is preferably a linear polymer. By making it a linear polymer, it is easy to cause the molecular chains to entangle with each other, and it is possible to expect an increase in cohesive force. Therefore, the resulting adhesive is easy to exert a suitable gel fraction and adhesion, etc., and it is easy to make the step tracking property under high temperature and high humidity conditions become excellent.
[0083] In addition, (meth) acrylate polymer (A) is preferably a solution polymer obtained by solution polymerization. By making it a solution polymer, a high molecular weight polymer can be easily obtained, and an increase in cohesive force can be expected. Therefore, the obtained adhesive is easy to exert suitable gel fraction and adhesion, etc., and is easy to make the step tracking property under high temperature and high humidity conditions become excellent.
[0084] The polymerization form of the (meth)acrylate polymer (A) may be a random copolymer or a block copolymer.
[0085] According to the following limit, the weight average molecular weight of the (meth) acrylate polymer (A) is preferably 200,000 or more, particularly preferably 300,000 or more, and further preferably 400,000 or more. If the lower limit of the weight average molecular weight of the (meth) acrylate polymer (A) is as above, the gel fraction and storage modulus of the obtained adhesive are easy to become appropriate, and the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, there is a tendency to make the dispersibility of the white colorant (C) in the adhesive good, so the reproducibility and uniformity of the above optical properties of the obtained adhesive become good, and it is easy to meet the above color difference ΔE*.
[0086] In addition, based on the upper limit, the weight average molecular weight of (meth) acrylate polymer (A) is preferably less than 2 million, more preferably less than 1.5 million, particularly preferably less than 1 million, and more preferably less than 800,000. If the upper limit of the weight average molecular weight of (meth) acrylate polymer (A) is above, the gel fraction and storage modulus of the obtained adhesive are easily appropriate, and the initial step tracking property becomes more excellent. In addition, the weight average molecular weight in this specification is the value converted by standard polystyrene measured by gel permeation chromatography (GPC) method.
[0087] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.
[0088] (1-2) Cross-linking agent (B)
[0089] The crosslinking agent (B) can crosslink the (meth)acrylate polymer (A) to form a good three-dimensional network structure by heating the adhesive composition P. This improves the cohesive force of the resulting adhesive and improves the step followability under high temperature and high humidity conditions.
[0090] As the crosslinking agent (B), any substance that reacts with the reactive group possessed by the (meth)acrylate polymer (A) may be used, for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. Among the above, it is preferred to use an isocyanate crosslinking agent that has excellent reactivity with the reactive group possessed by the (meth)acrylate polymer (A). In addition, the crosslinking agent (B) may be used alone or in combination of two or more.
[0091] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate; and their biuret bodies and isocyanurate bodies; and adducts as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among them, from the perspective of reactivity with hydroxyl groups, trimethylolpropane-modified aromatic polyisocyanates are preferred, and trimethylolpropane-modified toluene diisocyanate and trimethylolpropane-modified xylene diisocyanate are particularly preferred.
[0092] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more. In addition, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, particularly preferably 1 part by mass or less, and further preferably 0.4 parts by mass or less. By making the content of the crosslinking agent (B) within the above range, the obtained adhesive exerts good cohesive force, and the values of gel fraction and adhesion etc. are easily appropriate, and the step tracking property under high temperature and high humidity conditions becomes more excellent.
[0093] (1-3) White colorant (C)
[0094] The white colorant (C) is the above-mentioned white colorant, and the specific type and content thereof are as described above.
[0095] (1-4) Active energy ray-curable component (D)
[0096] It is speculated that in the adhesive obtained by curing the adhesive composition P cross-linked with active energy rays, the active energy ray-curable components (D) are polymerized with each other, and the polymerized active energy ray-curable components (D) are entangled in the cross-linked structure (three-dimensional network structure) of the (meth)acrylate polymer (A). The adhesive having a high-dimensional structure becomes particularly excellent in step tracking under high temperature and high humidity conditions.
[0097] The active energy ray-curable component (D) is not particularly limited as long as it is a component that is cured by irradiation with active energy rays and can obtain the above-mentioned effect, and can be any one of a monomer, an oligomer or a polymer, or a mixture of these substances. Among them, a multifunctional acrylate monomer having better step tracking properties under high temperature and high humidity conditions can be preferably cited.
[0098] Examples of the polyfunctional acrylate monomer include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, adipate neopentyl glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, di(acryloyloxyethyl) isocyanurate, allylated cyclohexyl di(meth)acrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxy)]
[0043] The present invention relates to a difunctional monomer such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, ε-caprolactone-modified tri(2-(meth)acryloyloxyethyl)isocyanurate, etc.; a tetrafunctional monomer such as diglycerol tetra(meth)acrylate and pentaerythritol tetra(meth)acrylate; a pentafunctional monomer such as propionic acid-modified dipentaerythritol penta(meth)acrylate; a hexafunctional monomer such as dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate, etc. These multifunctional acrylate monomers may be used alone or in combination of two or more. Furthermore, the molecular weight of the polyfunctional acrylate monomer is preferably less than 1,000 from the viewpoint of compatibility with the (meth)acrylate polymer (A).
[0099] When the adhesive composition P contains an active energy ray curable component (D), relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the active energy ray curable component (D) in the adhesive composition P is preferably more than 1 part by mass, particularly preferably more than 3 parts by mass, and more preferably more than 4 parts by mass, according to the following limit. On the other hand, from the perspective of the adhesion of the adhesive after active energy ray curing, according to the upper limit, the above content is preferably less than 30 parts by mass, particularly preferably less than 20 parts by mass, more preferably less than 14 parts by mass, and from the perspective of easily exerting a higher adhesion, preferably less than 9 parts by mass. By making the content of the active energy ray curable component (D) within the above range, the values of the gel fraction and adhesion of the adhesive after active energy ray curing are easily appropriate, and the step tracking property under high temperature and high humidity conditions becomes more excellent.
[0100] (1-5) Photopolymerization initiator (E)
[0101] When ultraviolet rays are used as the active energy rays for curing the adhesive composition P, it is preferred that the adhesive composition P further contains a photopolymerization initiator (E). By containing the photopolymerization initiator (E), the active energy ray-curable component (D) can be efficiently polymerized, and the polymerization curing time and the irradiation amount of the active energy rays can be reduced.
[0102] Examples of such a photopolymerization initiator (E) include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylenediphenyl Ketone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone], 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, etc. These photopolymerization initiators may be used alone or in combination of two or more.
[0103] When the adhesive composition P contains a photopolymerization initiator (E), the content of the photopolymerization initiator (E) in the adhesive composition P is preferably 0.1 parts by mass or more, particularly preferably 1 part by mass or more, and further preferably 5 parts by mass or more, based on the following limit, relative to 100 parts by mass of the active energy ray-curable component (D). In addition, based on the upper limit, it is preferably 30 parts by mass or less, particularly preferably 20 parts by mass or less, and further preferably 12 parts by mass or less.
[0104] (1-6) Various additives
[0105] Various additives commonly used in acrylic adhesives may be added to the adhesive composition P as needed, such as silane coupling agents, rust preventives, ultraviolet absorbers, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, refractive index adjusters, etc. In addition, the polymerization solvent or dilution solvent described later is not included in the additives constituting the adhesive composition P.
[0106] Among the above, the adhesive composition P preferably contains a silane coupling agent. This improves the adhesion to the adherend, whether it is a plastic plate or a glass member, and further improves the step followability under high temperature and high humidity conditions.
[0107] As the silane coupling agent, an organosilicon compound which has good compatibility with the (meth)acrylate polymer (A), is light-transmissive and has at least one alkoxysilyl group in the molecule is preferred.
[0108] Examples of the silane coupling agent include silicon compounds containing polymerizable unsaturated groups such as vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane; silicon compounds having epoxy structures such as 3-glycidoxypropyl trimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane; and silicon compounds containing mercapto groups such as 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl dimethoxymethylsilane. Silicon compounds containing amino groups such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; condensates of 3-chloropropyltrimethoxysilane, isocyanatepropyltriethoxysilane, or at least one of them and methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane, etc. These silane coupling agents can be used alone or in combination of two or more.
[0109] The content of the silane coupling agent in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylate polymer (A). In addition, the content is preferably 1 part by mass or less, particularly preferably 0.5 parts by mass or less, and further preferably 0.3 parts by mass or less.
[0110] (2) Preparation of adhesive composition
[0111] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), mixing the obtained (meth)acrylate polymer (A), a crosslinking agent (B) and a white colorant (C), and adding an active energy ray-curable component (D), a photopolymerization initiator (E), additives, etc. as needed.
[0112] The (meth)acrylate polymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer using a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. However, the present invention is not limited thereto, and polymerization can also be carried out without a solvent. Examples of polymerization solvents include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, and the like, and two or more thereof can also be used simultaneously.
[0113] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0114] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0115] Furthermore, in the above-mentioned polymerization step, by adding a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.
[0116] After obtaining the (meth)acrylate polymer (A), a crosslinking agent (B), a white colorant (C), and, if necessary, a diluting solvent, an active energy ray-curable component (D), a photopolymerization initiator (E), additives, etc. are added to the solution of the (meth)acrylate polymer (A), and the mixture is fully mixed to obtain a solvent-diluted adhesive composition P (coating solution). In addition, for any of the above components, when a solid substance is used, or when a precipitate is generated when mixed with other components in an undiluted state, the component can be dissolved or diluted in a diluting solvent alone in advance and then mixed with other components.
[0117] As the above-mentioned dilution solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and 1,2-dichloroethane; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-type solvents such as ethyl cellosolve, etc. can be used.
[0118] The concentration and viscosity of the coating solution prepared in this way are not particularly limited as long as they are within the range that can be applied, and can be appropriately selected according to the circumstances. For example, the adhesive composition P is diluted in a manner such that the concentration is 10 to 60% by mass. In addition, when obtaining the coating solution, it is not necessary to add a diluting solvent, etc. As long as the adhesive composition P is a viscosity that can be applied, etc., a diluting solvent may not be added. At this time, the adhesive composition P is a coating solution in which the polymerization solvent of the (meth)acrylate polymer (A) is directly used as a diluting solvent.
[0119] (3) Formation of Adhesive Layer
[0120] The adhesive layer 11 of the preferred embodiment is composed of an adhesive obtained by crosslinking (coating layer of) an adhesive composition P. The crosslinking of the adhesive composition P can usually be carried out by heat treatment. In addition, the drying process when the diluting solvent or the like is volatilized from the coating layer of the adhesive composition P applied on the desired object can also be used as the heat treatment.
[0121] The heating temperature of the heat treatment is preferably 50 to 150° C., particularly preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, particularly preferably 50 seconds to 2 minutes.
[0122] After the heat treatment, a 1-2 week aging period may be provided at room temperature (e.g., 23°C, 50% RH) as required. If the aging period is required, the adhesive is formed after the aging period. If the aging period is not required, the adhesive is formed directly after the heat treatment.
[0123] By the above-mentioned heating treatment (and aging), the (meth)acrylate polymer (A) is fully crosslinked via the crosslinking agent (B). The adhesive obtained in this way easily satisfies the required values of gel fraction, storage modulus, adhesive strength, etc., and has excellent step followability under high temperature and high humidity conditions.
[0124] (4) Physical properties of adhesive
[0125] (4-1) Gel fraction
[0126] According to the following limit values, the gel fraction of the adhesive constituting the adhesive layer 11 of the present embodiment is preferably 20% or more, more preferably 30% or more, particularly preferably 40% or more, further preferably 48% or more, and most preferably 55% or more. If the lower limit value of the gel fraction of the adhesive is as described above, the cohesive force of the adhesive becomes higher, and the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, according to the upper limit value, the gel fraction of the adhesive of the present embodiment is preferably 99% or less, more preferably 90% or less, particularly preferably 80% or less, and further preferably 74% or less. If the upper limit value of the gel fraction of the adhesive is as described above, the adhesive will not become too hard, and the initial step tracking property and the step tracking property under high temperature and high humidity conditions become excellent. In addition, good adhesion is exhibited, and the adhesion to the adherend becomes more excellent. Here, the method for determining the gel fraction of the adhesive is shown in the test example described later.
[0127] When the adhesive is active energy ray curable, the gel fraction of the adhesive after active energy ray curing is preferably 30% or more, more preferably 40% or more, particularly preferably 55% or more, and further preferably 65% or more, based on the following limit. In addition, based on the upper limit, the gel fraction is preferably 99% or less, more preferably 90% or less, particularly preferably 85% or less, and further preferably 80% or less. By making the gel fraction of the adhesive after active energy ray curing within the above range, the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, good adhesion is exhibited, and the adhesion to the adherend becomes more excellent.
[0128] (4-2) Storage modulus
[0129] In terms of the lower limit value, the storage modulus of the adhesive constituting the adhesive layer 11 in the present embodiment at 23°C is preferably 0.001 MPa or more, particularly preferably 0.01 MPa or more, further preferably 0.04 MPa or more, and most preferably 0.07 MPa or more. By setting the lower limit value of the above storage modulus as such, the step following property under high temperature and high humidity conditions becomes excellent. In addition, in terms of the upper limit value, the above storage modulus is preferably 3 MPa or less, particularly preferably 1 MPa or less, further preferably 0.5 MPa or less, and most preferably 0.2 MPa or less. By setting the upper limit value of the above storage modulus as such, the initial step following property becomes excellent. In addition, the storage modulus in this specification is a value measured by the torsional shear method (ねじりせん断法) at a measurement frequency of 1 Hz in accordance with JIS K7244-6. Specifically, as shown in the test examples described later.
[0130] When the adhesive is a radiation curable adhesive, in terms of the lower limit value, the storage modulus of the adhesive after radiation curing at 23°C is preferably 0.10 MPa or more, more preferably 0.15 MPa or more, particularly preferably 0.20 MPa or more, and further preferably 0.25 MPa or more. By setting the lower limit value of the above storage modulus as such, the step following property under high temperature and high humidity conditions becomes even more excellent. In addition, in terms of the upper limit value, the above storage modulus is preferably 5 MPa or less, particularly preferably 1 MPa or less, and further preferably 0.5 MPa or less. By setting the upper limit value of the above storage modulus as such, the adhesiveness becomes excellent.
[0131] 1-2. Release sheet
[0132] The release sheets 12a and 12b protect the adhesive layer 11 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (adhesive layer 11) is used. In the adhesive sheet 1 of the present embodiment, one or both of the release sheets 12a and 12b are not essential.
[0133] As the release sheets 12a and 12b, for example, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polyethylene naphthalate film, a polybutylene terephthalate film, a polyurethane film, an ethylene-vinyl acetate film, an ionomer resin film, an ethylene-(meth)acrylic acid copolymer film, an ethylene-(meth)acrylate copolymer film, a polystyrene film, a polycarbonate film, a polyimide film, a fluororesin film, etc. can be used. In addition, a crosslinked film of these films can also be used. Further, it can also be a laminated film of these films.
[0134] It is preferred that the release surfaces of the release sheets 12a and 12b (particularly the surfaces in contact with the adhesive layer 11) be subjected to a release treatment. Examples of release agents used for the release treatment include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax release agents. In addition, it is preferred that one of the release sheets 12a and 12b be a heavy release type release sheet having a larger release force, and the other be a light release type release sheet having a smaller release force.
[0135] The thickness of the release sheets 12a and 12b is not particularly limited, but is generally about 20 to 150 μm.
[0136] 2.Physical properties
[0137] (1) Adhesion
[0138] According to the following limit, the adhesive sheet 1 of the present embodiment preferably has an adhesion of 1N / 25mm or more to soda-lime glass, more preferably 5N / 25mm or more, particularly preferably 10N / 25mm or more, and further preferably 15N / 25mm or more. If the lower limit of the adhesion is as described above, the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, according to the upper limit, the above-mentioned adhesion is preferably 70N / 25mm or less, more preferably 60N / 25mm or less, and particularly preferably 50N / 25mm or less. If the upper limit of the adhesion is as described above, good reoperability can be obtained, and when a lamination error occurs, the display body constituent member, especially the expensive display body constituent member, can be reused.
[0139] When the adhesive constituting the adhesive layer 11 is an active energy ray-curable adhesive, according to the following limit, the adhesive sheet 1 of the present embodiment is preferably 5N / 25mm or more, more preferably 10N / 25mm or more, particularly preferably 20N / 25mm or more, and further preferably 25N / 25mm or more after irradiating the active energy ray. If the lower limit of the adhesive force is as above, the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, according to the upper limit, the above-mentioned adhesive force is preferably 70N / 25mm or less, more preferably 60N / 25mm or less, and particularly preferably 50N / 25mm or less. If the upper limit of the adhesive force is as above, good reoperability can be obtained, and when a lamination error occurs, the display body constituent member, especially the expensive display body constituent member, can be reused.
[0140] Here, the adhesive strength in this specification refers to the adhesive strength measured by the 180-degree peeling method based on JIS Z0237:2009, which is a value measured by attaching a measurement sample to an adherend with a width of 25 mm and a length of 100 mm, pressing the sample at 0.5 MPa and 50°C for 20 minutes, leaving the sample under normal pressure, 23°C, and 50% RH for 24 hours, and then peeling the sample at a speed of 300 mm / min. In addition, the adhesive strength after active energy ray irradiation refers to the adhesive strength of the adhesive layer that has been cured by irradiating the active energy ray after being attached to the adherend.
[0141] (2) Segment Following Rate
[0142] Regarding the step tracking property under high temperature and high humidity conditions, the step tracking rate (%) represented by the following formula of the adhesive layer 11 is preferably 5% or more, more preferably 10% or more, particularly preferably 20% or more, further preferably 30% or more, and most preferably 40% or more. Thus, the step tracking property under high temperature and high humidity conditions can be excellent, and at this time, the initial step tracking property (during lamination) is also excellent. In addition, the upper limit of the step tracking rate is not particularly limited, but is generally preferably 80% or less, and particularly preferably 70% or less.
[0143] Step following rate (%) = {(height of the step that is embedded without bubbles, floating, peeling, etc. after the specified durability test (μm)) / (thickness of the adhesive layer)}×100
[0144] The test method of the step followability is as described in the test examples below. In addition, for an active energy ray-curable adhesive layer, the step followability refers to the step followability of the adhesive layer that is attached to an adherend and then irradiated with active energy rays to be cured.
[0145] 3. Manufacturing of adhesive sheet
[0146] As a manufacturing example of the adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of a release sheet 12a (or 12b), and a heat treatment is performed to thermally crosslink the adhesive composition P. After forming a coating layer, the coating layer is superimposed on the release surface of another release sheet 12b (or 12a). When a maturation period is required, the coating layer becomes the adhesive layer 11 by setting the maturation period. When a maturation period is not required, the coating layer directly becomes the adhesive layer 11. Thus, the adhesive sheet 1 can be obtained. The conditions for the heat treatment and maturation are as described above.
[0147] As another manufacturing example of the adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of a release sheet 12a, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 12a with a coating layer. In addition, a coating solution of the adhesive composition P is applied to the release surface of another release sheet 12b, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 12b with a coating layer. Then, the release sheet 12a with a coating layer and the release sheet 12b with a coating layer are laminated in such a manner that the two coating layers are in contact with each other. Here, a plurality of release sheets with coating layers can be prepared, and the required number of coating layers can be laminated. When a aging period is required, the laminated coating layer becomes an adhesive layer 11 by setting a aging period, and when a aging period is not required, the laminated coating layer directly becomes an adhesive layer 11. Thus, the adhesive sheet 1 can be obtained. According to this production example, even when the pressure-sensitive adhesive layer 11 is thick, stable production can be performed.
[0148] As a method for applying the coating solution of the adhesive composition P, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be used.
[0149] [Display Body]
[0150] As the type of display body (display) of this embodiment, for example, a display body of a television, a computer monitor, a monitor of various devices, a digital signage, a smart phone, a tablet terminal, etc. can be listed. For these display bodies, sometimes it is required to have an appearance coordination with white surrounding components, such as a white frame material, a white wall, a white printing part, etc. However, the display body of the present invention is not limited to this.
[0151] like Figure 2 As shown, the display body 2 of this embodiment is composed of a first display body constituent member 21 (one display body constituent member), a second display body constituent member 22 (another display body constituent member) and an adhesive layer 11, and the adhesive layer 11 is located between the first display body constituent member 21 and the second display body constituent member 22, and adheres the first display body constituent member 21 and the second display body constituent member 22 to each other.
[0152] At least one of the first display body constituent member 21 and the second display body constituent member 22 may have a step on the surface on the side to be bonded to the pressure-sensitive adhesive layer 11 . Figure 2 In the illustrated embodiment, the first display constituent member 21 has a step such as the printed layer 3 on the surface on the adhesive layer 11 side.
[0153] The adhesive layer 11 in the display 2 is formed of the adhesive layer 11 of the adhesive sheet 1. Specifically, the adhesive layer 11 in the display 2 may be the adhesive layer 11 of the adhesive sheet 1 itself, or may be formed by curing the adhesive layer 11 with active energy rays.
[0154] The display 2 may be, for example, a liquid crystal display (LCD), a light emitting diode (LED) display, an organic electroluminescent (organic EL) display, electronic paper, or the like, and may be a touch panel or a member constituting part of these.
[0155] The first display component 21 is preferably a protective panel composed of a laminate including a glass plate, a plastic plate, etc. In this case, the printed layer 3 is usually formed in a frame shape on the adhesive layer 11 side of the first display component 21 .
[0156] The glass plate is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, barium-strontium-containing glass, aluminosilicate glass, lead glass, borosilicate glass, barium borosilicate glass, etc. The thickness of the glass plate is not particularly limited, but is usually 0.1 to 5 mm, preferably 0.2 to 2 mm.
[0157] The plastic plate is not particularly limited, and examples thereof include acrylic plates, polycarbonate plates, etc. The thickness of the plastic plate is not particularly limited, but is usually 0.2 to 5 mm, preferably 0.4 to 3 mm.
[0158] In addition, various functional layers (transparent conductive film, metal layer, silicon dioxide layer, hard coating layer, anti-glare layer, etc.) may be provided on one or both sides of the glass plate or plastic plate, and optical components may be laminated. In addition, the transparent conductive film and the metal layer may also be patterned.
[0159] The second display component 22 is preferably an optical member to be attached to the first display component 21, a display module (for example, a liquid crystal module, a light emitting diode (LED) module, an organic electroluminescent (organic EL) module, etc.), or a laminate including a display module.
[0160] Examples of the optical member include an anti-scattering film, a polarizing film, a phase difference film, a viewing angle compensation film, a brightness enhancement film, a contrast enhancement film, a liquid crystal polymer film, a diffusion film, a semi-transmissive reflective film, a transparent conductive film, and a film sensor. Examples of the anti-scattering film include a hard coating film formed on one side of a substrate film.
[0161] The color of the printed layer 3 of the present embodiment is preferably white. The material constituting the printed layer 3 is not particularly limited, and known materials for printing can be used. The lower limit of the thickness of the printed layer 3, that is, the height of the step is preferably 3 μm or more, more preferably 5 μm or more, particularly preferably 7 μm or more, and most preferably 10 μm or more. By making the lower limit value above or above, it is possible to fully ensure the concealment of the electrical wiring, etc., which cannot be seen from the observer's side. In addition, the upper limit value is preferably 200 μm or less, more preferably 100 μm or less, and particularly preferably 30 μm or less. By making the upper limit value below the above, it is possible to prevent the adhesive layer 11 from deteriorating the step tracking property of the printed layer 3.
[0162] To produce the display 2 , as an example, one release sheet 12 a of the adhesive sheet 1 is peeled off, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to the surface of the first display component 21 on the side where the printed layer 3 exists.
[0163] Then, another release sheet 12b is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the exposed adhesive layer 11 of the adhesive sheet 1 is laminated to the second display component 22. In another example, the lamination order of the first display component 21 and the second display component 22 may be reversed.
[0164] When the adhesive layer 11 is active energy ray-curable, after the first display body constituent member 21 and the second display body constituent member 22 are attached via the adhesive layer 11 as described above, the active energy ray is irradiated to the adhesive layer 11. As a result, the energy ray-curable component (D) in the adhesive layer 11 is polymerized, and the adhesive layer 11 is cured. The irradiation of the adhesive layer 11 with energy rays is usually performed via either the first display body constituent member 21 or the second display body constituent member 22, preferably via the first display body constituent member 21 as a protective panel.
[0165] The active energy ray refers to an active energy ray having an energy quantum among electromagnetic waves or charged particle beams, and specific examples thereof include ultraviolet rays and electron beams, etc. Among the active energy rays, ultraviolet rays are particularly preferred because they are easy to handle.
[0166] The ultraviolet irradiation can be performed using a high pressure mercury lamp, a fusion H lamp, a xenon lamp, etc. The ultraviolet irradiation amount is preferably 50 to 1000 mW / cm 2 About 100 to 500 mW / cm 2 In addition, the light intensity is preferably 50 to 10000 mJ / cm 2 , more preferably 200 to 7000 mJ / cm 2 , particularly preferably 500 to 3000 mJ / cm 2On the other hand, the electron beam irradiation can be performed using an electron beam accelerator or the like, and the irradiation amount of the electron beam is preferably about 10 to 1000 krad.
[0167] Here, if Figure 3 As shown, the display body 2 of this embodiment may include a white frame material 4 around the display body 2 .
[0168] The display body 2 has an excellent appearance coordination with the white frame material 4 by virtue of the physical properties of the adhesive layer 11. In addition, the display body 2 has a good visibility as a display body.
[0169] Furthermore, in the above-mentioned display body 2, when the adhesive layer 11 is formed by the adhesive composition P, the adhesive layer 11 has excellent step tracking properties under high temperature and high humidity conditions. Therefore, for example, even when the display body 2 is placed under high temperature and high humidity conditions (for example, 85°C, 85% RH), the generation of bubbles, floating, peeling, etc. near the step can be suppressed.
[0170] The above-described embodiments are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above-described embodiments also encompasses all design changes and equivalents within the technical scope of the present invention.
[0171] For example, any one or both of the release sheets 12a and 12b in the adhesive sheet 1 may be omitted, and further, required optical components may be laminated to replace the release sheets 12a and / or 12b. In addition, the first display component 21 may not have a step difference. Further, not only the first display component 21, but also the second display component 22 may have a step difference on the adhesive layer 11 side.
[0172] Example
[0173] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.
[0174] [Example 1]
[0175] 1. Preparation of (meth)acrylate polymers
[0176] 70 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of methyl methacrylate and 15 parts by mass of 2-hydroxyethyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylate polymer (A). The molecular weight of the (meth)acrylate polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 700,000.
[0177] 2. Preparation of adhesive composition
[0178] 100 parts by mass (solid content conversion value; the same below) of the (meth)acrylate polymer (A) obtained in the above step 1, 0.2 parts by mass of trimethylolpropane-modified toluene diisocyanate (manufactured by TOYOCHEM CO., LTD., product name "BHS8515") as a crosslinking agent (B), 1.0 parts by mass of a titanium oxide colorant as a white colorant (C), and 0.2 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed and stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition.
[0179] Table 1 shows the respective proportions (solid content conversion value) of the adhesive composition when the (meth)acrylate polymer (A) is 100 parts by mass (solid content conversion value). The details of the abbreviations and the like described in Table 1 are as follows.
[0180] [(Meth)acrylate polymer (A)]
[0181] 2EHA: 2-Ethylhexyl acrylate
[0182] MMA: Methyl Methacrylate
[0183] HEA: 2-Hydroxyethyl Acrylate
[0184] IBXA: Isobornyl acrylate
[0185] ACMO: N-acryloylmorpholine
[0186] BA: n-butyl acrylate
[0187] AA: Acrylic acid
[0188] [Crosslinking agent (B)]
[0189] TDI: Trimethylolpropane-modified toluene diisocyanate (manufactured by TOYOCHEM CO., LTD., product name "BHS8515")
[0190] XDI: trimethylolpropane-modified xylylene diisocyanate (manufactured by Soken Chemical & Engineering Co., Ltd., product name "TD-75")
[0191] The composition of the titanium oxide colorant as the white colorant (C) is: 91.2 mass % of titanium oxide, 0.8 mass % of zinc oxide, and 8 mass % of silicon dioxide. The mode diameter of the titanium oxide colorant is 420 nm, and the median particle size is 420 nm. The particle size is measured by a dynamic light scattering method (manufactured by MicrotracBEL Corp., device name: Nanotrac Wave).
[0192] 3. Manufacturing of adhesive sheet
[0193] The coating solution of the adhesive composition obtained in the above step 2 was applied to the release-treated surface of a heavy-release release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") having one side of a polyethylene terephthalate film subjected to release treatment using a silicone release agent using a knife coater. Then, the coating layer was heated at 90° C. for 1 minute to form a coating layer (thickness: 50 μm), thereby preparing a heavy-release release sheet with a coating layer.
[0194] On the other hand, the coating solution of the adhesive composition obtained in the above step 2 was applied to the release-treated surface of a light-release release sheet (manufactured by LINTEC Corporation, product name "SP-PET382120") having one side of a polyethylene terephthalate film subjected to release treatment using a silicone release agent using a knife coater. Then, the coating layer was heated at 90° C. for 1 minute to form a coating layer (thickness: 50 μm), thereby preparing a light-release release sheet with a coating layer.
[0195] The coating layer side surface of the heavy release sheet with coating layer obtained above was bonded to the coating layer side surface of the light release sheet with coating layer obtained above to obtain a laminated body in which the coating layer with a thickness of 100 μm was sandwiched between the heavy release sheet and the light release sheet.
[0196] Then, the laminate was aged for 7 days under the conditions of 23° C. and 50% RH to produce an adhesive sheet having a structure of heavy-release release sheet / adhesive layer (thickness: 100 μm) / light-release release sheet.
[0197] The thickness of the adhesive layer is a value measured using a constant pressure thickness tester (manufactured by TECLOCK CO., LTD., product name “PG-02”) in accordance with JIS K7130.
[0198] [Examples 2 to 10, Comparative Examples 1 to 2]
[0199] An adhesive sheet was produced in the same manner as in Example 1 except that the type and ratio of each monomer constituting the (meth)acrylate polymer (A), the weight average molecular weight (Mw) of the (meth)acrylate polymer (A), the type of the crosslinking agent (B), the blending amount of the white colorant (C), and the thickness of the adhesive layer were changed to those shown in Table 1. In Examples 6 to 9, an adhesive composition further blended with 5 parts by mass of ε-caprolactone-modified tris(2-acryloyloxyethyl)isocyanurate (manufactured by SHIN-NAKAMURA CHEMICAL CO., LTD., product name "NK ester A-9300-1CL") as an active energy ray-curable component (D) and 0.5 parts by mass of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide as a photopolymerization initiator (E) was prepared, and an active energy ray-curable adhesive layer was formed using the adhesive composition. In addition, the thickness of the adhesive layer formed on the release sheet was changed and the number of layers was changed to change the thickness of the adhesive layer.
[0200] The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight measured under the following conditions using gel permeation chromatography (GPC) (GPC measurement).
[0201] <Measurement Conditions>
[0202] ·GPC measuring apparatus: HLC-8020 manufactured by TOSOH CORPORATION
[0203] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION
[0204] TSK guard column HXL-H
[0205] TSK gel GMHXL (×2)
[0206] TSK gel G2000HXL
[0207] ·Test solvent: tetrahydrofuran
[0208] ·Measurement temperature: 40℃
[0209] [Test Example 1] (Measurement of gel fraction)
[0210] The adhesive sheets obtained in the examples and comparative examples were cut into a size of 80 mm x 80 mm, and the adhesive layer was wrapped in a polyester net (mesh size 200), and the mass was weighed using a precision balance, and the mass of the adhesive itself was calculated by subtracting the mass of the net alone. The mass at this time was recorded as M1.
[0211] Next, at room temperature (23°C), immerse the adhesive wrapped in the polyester net in ethyl acetate for 24 hours. Then, take out the adhesive, air-dry it for 24 hours at a temperature of 23°C and a relative humidity of 50%, and further dry it in an oven at 80°C for 12 hours. After drying, weigh its mass with a precision balance, subtract the mass of the net alone, and calculate the mass of the adhesive itself. The mass at this time is recorded as M2. The gel fraction (%) is expressed as (M2 / M1)×100. Thus, the gel fraction of the adhesive (before UV irradiation) is derived. The results are shown in Table 2.
[0212] On the other hand, the adhesive layer of the adhesive sheet obtained in Examples 6 to 9 was irradiated with active energy rays (ultraviolet rays; UV) through a light-peelable release sheet under the following conditions to cure the adhesive layer. The gel fraction of the adhesive of the cured adhesive layer (after UV irradiation) was derived in the same manner as above. The results are shown in Table 2.
[0213] <Active Energy Ray Irradiation Conditions>
[0214] Use high pressure mercury lamp
[0215] Illuminance 200mW / cm 2 , light intensity 2000mJ / cm 2
[0216] · UV illuminance-light meter used is "UVPF-A1" manufactured by Eye graphics Co., Ltd.
[0217] [Test Example 2] (Measurement of L*a*b*)
[0218] The light release type release sheet was peeled off from the adhesive sheet obtained in the examples and comparative examples, and the exposed adhesive layer was attached to a soda lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd.). Next, the heavy release type release sheet was peeled off from the adhesive layer, and the polycarbonate resin plate side surface of a plastic plate (manufactured by MITSUBISHIGAS CHEMICAL COMPANY, INC., product name "Iupilon sheet MR58U", thickness: 1 mm) on which a polymethyl methacrylate resin layer was laminated on a polycarbonate resin plate was attached to the exposed adhesive layer to prepare a sample.
[0219] The lightness L* (L*M), chromaticity a* (a*M) and chromaticity b* (b*M) specified by the CIE1976 L*a*b* colorimetric system were measured for the plastic plate side of the obtained sample using a simultaneous photometric spectrophotometer (manufactured by NIPPONDENSHOKU INDUSTRIES Co., LTD., product name "SQ2000"). In addition, the color difference ΔE* was calculated based on the above results by the following formula (I). The results are shown in Table 2.
[0220] [Mathematical formula 2]
[0221]
[0222] [Test Example 3] (Measurement of total light transmittance)
[0223] The adhesive layer of the adhesive sheet obtained in the embodiment and the comparative example was bonded to glass, which was used as a sample for measurement. Based on the background measurement using glass, the total light transmittance (%) of the above-mentioned sample for measurement was measured using a haze meter (manufactured by NIPPON DENSHOKU INDUSTRIES Co., LTD., product name "NDH-5000") in accordance with JIS K7361-1:1997. The results are shown in Table 2.
[0224] [Test Example 4] (Measurement of Haze Value)
[0225] The adhesive layer of the adhesive sheet obtained in the embodiment and the comparative example was bonded to glass, which was used as a sample for measurement. Based on the background measurement using glass, the haze value (total light haze value; %) of the above-mentioned sample for measurement was measured using a haze meter (manufactured by NIPPONDENSHOKU INDUSTRIES Co., LTD., product name "NDH-5000") in accordance with JIS K7136:2000. The results are shown in Table 2.
[0226] [Test Example 5] (Measurement of storage modulus)
[0227] The release sheets were peeled off from the adhesive sheets obtained in Examples and Comparative Examples, and a plurality of adhesive layers were laminated to a thickness of 3 mm. A cylinder having a diameter of 8 mm (height of 3 mm) was punched out from the laminate of the obtained adhesive layers to prepare a sample.
[0228] The storage modulus (MPa; before UV irradiation) of the above samples was measured by a torsional shear method under the following conditions using a viscoelasticity measuring apparatus (manufactured by Physica Corporation, product name “MCR300”) in accordance with JIS K7244-6.
[0229] Measuring frequency: 1Hz
[0230] Measurement temperature: 23°C
[0231] In addition, the adhesive layer of the adhesive sheet obtained in Examples 6 to 9 was irradiated with active energy rays (ultraviolet rays; UV) through a light-peelable release sheet under the same conditions as in Test Example 1 to cure the adhesive layer. The storage modulus (after UV irradiation) of the adhesive of the cured adhesive layer was derived in the same manner as above. The results are shown in Table 2.
[0232] [Test Example 6] (Measurement of Adhesive Strength)
[0233] The light release type release sheet was peeled off from the adhesive sheet obtained in the examples and comparative examples, and the exposed adhesive layer was attached to the easy adhesive layer of a polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET A4300", thickness: 100 μm) having an easy adhesive layer to obtain a laminate of heavy release type release sheet / adhesive layer / PET. The obtained laminate was cut into 25 mm wide and 100 mm long, and used as a sample.
[0234] Under the environment of 23°C and 50% RH, the heavy release type release sheet was peeled off from the above sample, and the exposed adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.), and then pressurized at 0.5 MPa and 50°C for 20 minutes using an autoclave manufactured by KURIHARA SEISAKUSHO Co., Ltd. Then, it was left to stand under the conditions of 23°C and 50% RH for 24 hours.
[0235] Next, using a tensile tester (manufactured by ORIENTEC CORPORATION, product name "TENSILON"), the adhesive force (before UV irradiation; N / 25 mm) was measured at a peeling speed of 300 mm / min and a peeling angle of 180 degrees. The conditions not described here were measured in accordance with JIS Z0237:2009. The results are shown in Table 2.
[0236] In Examples 6 to 9, the adhesive layer was attached to the soda lime glass in the same manner as above, and then irradiated with active energy rays through the PET film under the same conditions as in Test Example 1, and the adhesive strength after curing the adhesive layer (after UV irradiation) was measured. The results are shown in Table 2.
[0237] [Test Example 7] (Measurement of step-difference following rate)
[0238] On the surface of a glass plate (manufactured by NSG Precision, product name "Corning Glass Eagle XG", length 90 mm × width 50 mm × thickness 0.5 mm), ultraviolet curing ink (manufactured by Teikoku Printing Inks Mfg. Co., Ltd., product name "POS-911 ink") was screen-printed in a predetermined thickness into a frame shape (outer shape: length 90 mm × width 50 mm, width 5 mm). Then, ultraviolet rays (80 W / cm 2 , 2 metal halide lamps, lamp height 15 cm, belt speed 10-15 m / min), the printed ultraviolet curing ink is cured to produce a glass plate with a step difference based on the printing (the height of the step difference: any one of 110μm, 30μm, 15μm, 12.5μm, 10μm, 7.5μm, and 5μm).
[0239] The light peeling type release sheet was peeled off from the adhesive sheet obtained in the embodiment and the comparative example, and the exposed adhesive layer was bonded to the easy adhesive layer of the polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET A4300", thickness: 100 μm) having an easy adhesive layer. Then, the heavy peeling type release sheet was peeled off to expose the adhesive layer, and a laminator (manufactured by FUJIPLA Inc., product name "LPD3214") was used to laminate the exposed adhesive layer on each glass plate with a step difference so that the adhesive layer covers the entire frame-shaped printing surface. Then, the pressure heat treatment was performed at 50°C and 0.5MPa for 20 minutes, and the film was placed at normal pressure, 23°C, and 50%RH for 24 hours.
[0240] In Examples 6 to 9, the adhesive layer was cured by irradiating active energy rays through the PET film under the same conditions as in Test Example 1. Then, the adhesive layer was stored under high temperature and high humidity conditions of 85°C and 85%RH for 72 hours (durability test). Then, the step followability was recorded as the step follow rate (%) shown in the following formula and evaluated. The results are shown in Table 2.
[0241] Step following rate (%) = [(height of the step that is embedded without bubbles, floating, peeling, etc. after the durability test (μm)) / (thickness of the adhesive layer)] × 100
[0242] [Test Example 8] (Evaluation of black concealment and appearance coordination)
[0243] The adhesive sheets obtained in the examples and comparative examples were cut into 70 mm long × 70 mm wide, and the adhesive layer of the adhesive sheet was sandwiched between two sheets of soda-lime glass (manufactured by Nippon Sheet Glass Co., Ltd., 70 mm long × 70 mm wide × 1.1 mm thick) and laminated to prepare samples. In Examples 6 to 9, active energy rays were irradiated through a soda-lime glass plate under the same conditions as in Test Example 1 to cure the adhesive layer, and the samples were prepared.
[0244] The obtained sample was laminated on the entire surface of a tablet terminal (manufactured by Apple Inc., product name "iPad (registered trademark)", pixel density: 264ppi, with frame-shaped white printed part) with the light turned off, including both the display part (black) and the frame-shaped white printed part. The black concealing property and appearance harmony of the sample were evaluated by naked eyes according to the following criteria. The results are shown in Table 2.
[0245] <Evaluation criteria for black concealment>
[0246] ◎···No matter what the viewing angle is, everything is white, and the black on the display is not visible at all.
[0247] 〇···When viewed from an oblique direction, the display appears white and the black color of the display is not visible at all, but when viewed from the front, the black color of the display is slightly visible.
[0248] △···The black color of the display is indeed suppressed, but the black color of the display is visible when viewed from an oblique direction.
[0249] ×···The black color of the display is very obvious even when viewed from an oblique direction.
[0250] <Evaluation criteria for appearance coordination>
[0251] ◎···No matter what the viewing angle is, it is difficult to distinguish the boundary between the display part and the white printed part of the tablet terminal.
[0252] ○···The boundary between the display portion and the white printed portion of the tablet terminal is difficult to discern when viewed from the front, but the boundary can be clearly discerned by changing the viewing angle.
[0253] △···Even when viewed from the front, the boundary between the display part and the white printed part of the tablet terminal can be distinguished, but the effect of setting up the sample has been confirmed.
[0254] ×···Even when viewed from the front, the visibility of the boundary between the display portion and the white printed portion of the tablet terminal does not change compared to the case where no sample is provided.
[0255] [Test Example 9] (Evaluation of visibility)
[0256] On a 15.6-inch display with a resolution of 1366×768 (manufactured by Fujitsu Limited, product name "LITEBOOK A574 / H"), various black characters (font: MS PGothic; "あ" to "ん", "A" to "Z" and "0" to "9") are displayed at 100% size and 10.5 points against a white background.
[0257] The sample obtained in Test Example 8 was placed on the above display. Furthermore, whether or not the characters were recognizable was confirmed with the naked eye at a distance of 50 cm from the display, and visibility was evaluated according to the following criteria.
[0258] The results are shown in Table 2.
[0259] ◎: All characters can be recognized.
[0260] ○: Some characters cannot be recognized depending on the type of the characters.
[0261] ×: Most of the characters cannot be recognized.
[0262] [Table 1]
[0263]
[0264]
[0265] As can be seen from Table 2, the display using the adhesive sheet obtained in the example is excellent in black concealing property, coordination with the white body, and visibility.
[0266] Industrial Applicability
[0267] The adhesive sheet of the present invention can be suitably used for bonding display component members together in, for example, a display having a white frame material or a display hung on a white wall.
Claims
1. An adhesive sheet comprising an adhesive layer for bonding one display component to another display component, wherein: The color difference ΔE* between the adhesive layer and pure white as specified by the CIE1976 L*a*b* color system is less than 95, The total light transmittance of the adhesive layer is greater than 10%. The haze value of the adhesive layer is 5% to 99.9%. The adhesive layer is composed of an acrylic adhesive containing a white colorant and a silane coupling agent.
2. The adhesive sheet according to claim 1, characterized in that The content of the white colorant in the adhesive is 0.01 mass % or more and 50 mass % or less.
3. The adhesive sheet according to claim 1, characterized in that The adhesive is obtained by cross-linking an adhesive composition containing at least a (meth)acrylate polymer (A), a cross-linking agent (B), and a white colorant (C).
4. The adhesive sheet according to claim 1, characterized in that The adhesive layer includes two release sheets and the adhesive layer, and the adhesive layer is sandwiched by the release sheets in a manner of contacting release surfaces of the two release sheets.
5. A display body comprising: a display body constituent member, another display body constituent member, and an adhesive layer for bonding the one display body constituent member and the other display body constituent member to each other, wherein the display body is characterized in that the adhesive layer is formed by the adhesive layer of the adhesive sheet according to any one of claims 1 to 4.
6. The display according to claim 5, characterized in that: At least one of the one display constituent member and the other display constituent member has a step on a surface on a side to be bonded by the adhesive layer.
7. The display according to claim 5, characterized in that: It has a white surrounding member.
Citation Information
Patent Citations
Functional adhesive sheet and flat panel-type display device
JP2005082634A
Optical adhesive, optical adhesive sheet and layered assembly
CN102994020A
Adhesive composition and adhesive sheet
CN107109164A
Composition for optical members, optical member and image display device
CN110249242A
Tacky adhesive for surface light source body
JP2001042107A